2001
DOI: 10.1097/00001756-200105080-00032
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of sensory deficits underlying the aphasia-like behavior of macaques with auditory cortex lesions

Abstract: Bilateral auditory cortex lesions in Japanese macaques result in an aphasia-like deficit in which the animals are unable to discriminate two forms of their coo vocalizations. To determine whether this deficit is sensory in nature, two monkeys with bilateral lesions were tested for their ability to discriminate frequency and frequency change. The results indicated that although the animals were able to discriminate between sounds of different frequencies, they were unable to determine whether a sound was changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 17 publications
3
42
0
Order By: Relevance
“…Postoperatively, frequency difference thresholds increased in the range of 7-25 Hz from preoperative thresholds (Weber fractions increased between 1.4 and 4.9%), and the size of the increase correlated with the size of the lesion. Harrington et al (2001) reported that two Japanese macaques with near-complete bilateral lesions of superior temporal cortex had pure tone frequency difference thresholds that were over twice those of two monkeys without lesions (center frequency near 625 Hz). The average Weber fraction associated with discrimination scores less than 0.80 [hit rate 溪 (hit rate 汐 false alarm rate)] was 5.8% compared with 2.4% in monkeys without superior temporal lesions.…”
Section: Functional Effects Of Auditory Cortex Lesions In Primatesmentioning
confidence: 99%
“…Postoperatively, frequency difference thresholds increased in the range of 7-25 Hz from preoperative thresholds (Weber fractions increased between 1.4 and 4.9%), and the size of the increase correlated with the size of the lesion. Harrington et al (2001) reported that two Japanese macaques with near-complete bilateral lesions of superior temporal cortex had pure tone frequency difference thresholds that were over twice those of two monkeys without lesions (center frequency near 625 Hz). The average Weber fraction associated with discrimination scores less than 0.80 [hit rate 溪 (hit rate 汐 false alarm rate)] was 5.8% compared with 2.4% in monkeys without superior temporal lesions.…”
Section: Functional Effects Of Auditory Cortex Lesions In Primatesmentioning
confidence: 99%
“…Physiological studies have shown that ACx neurons respond to spectrotemporally complex stimuli such as frequency-modulated (FM) stimuli, at times better than they respond to pure tones Phillips et al, 1985;Rauschecker and Tian, 2000;Tian and Rauschecker, 2004;WhitWeld and Evans, 1965). Conversely, lesions of ACx in animals diminish their ability to discriminate FM stimuli (Harrington et al, 2001;Kelly and WhitWeld, 1971;Ohl et al, 1999;Wetzel et al, 1998). ACx lesions in humans indicate a role in speech perception, or perhaps more precisely, in the perception of temporal or spectrotemporal transitions in speech (Phillips, 1998;Phillips and Farmer, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Auditory cortex is involved in the perception of temporal distinctions (Merzenich et al 1993). Humans, non-human primates, and rodents exhibit temporal processing deficits after auditory cortex lesions (Clark et al 2000a,b;Fitch et al 1994;Harrington et al 2001;Herman et al 1997;Mummery et al 1999).…”
Section: Introductionmentioning
confidence: 99%